EBMT prospective observational study on allogeneic hematopoietic stem cell transplantation in T-prolymphocytic leukemia (T-PLL) - Jędrzejczak, Wiesław; Sellner, Leopold; Dreger, Peter (Bone marrow transplantation, 2019)
Preliminary data suggest that allogeneic stem cell transplantation (allo-SCT) may be effective in T-prolymphocytic leukemia (T-PLL). The purpose of the present observational study was to assess the outcome of allo-SCT in patients aged 65 years or younger with a centrally confirmed diagnosis of T-PLL. Patients were consecutively registered with the EBMT at the time of transplantation and followed by routine EBMT monitoring but with an extended dataset. Between 2007 and 2012, 37 evaluable patients (median age 56 years) were accrued. Pre-treatment contained alemtuzumab in 95% of patients. Sixty-two percent were in complete remission (CR) at the time of allo-SCT. Conditioning contained total body irradiation with 6 Gy or more (TBI6) in 30% of patients. With a median follow-up of 50 months, the 4-year non-relapse mortality, relapse incidence, progression-free (PFS) and overall survival were 32, 38, 30 and 42%, respectively. By univariate analysis, TBI6 in the conditioning was the only significant predictor for a low relapse risk, and an interval between diagnosis and allo-SCT of more than 12 months was associated with a lower NRM. This study confirms for the first time prospectively that allo-SCT can provide long-term disease control in a sizable albeit limited proportion of patients with T-PLL.